Fenomena Pelayanan Jasa Transportasi Online Gojek Pada Mahasiswa Universitas Pembangunan Jaya - Amany Rania Azzahra; Asyila Shamara; Mohamad Zein Saleh (Shofanah Media Berkah, 2023)
Transportation refers to the process of moving people or goods from one location to another, utilizing vehicles operated by humans or machines. It plays a crucial role in enabling individuals to conduct their daily activities efficiently. In Indonesia, one specific mode of transportation is motorcycle taxis. The rapid advancement of information technology, especially the growth of the internet, has a significant impact on digital transformation. One form of this transformation is the shift from conventional motorcycle taxis to online motorcycle taxis, where bookings are made through smartphones and the Gojek app. The convenience offered by online motorcycle taxi services is gradually eroding the existence of conventional motorcycle taxis. This research is based on the phenomenon of the increasing use of online transportation services by the Indonesian public, especially university students. The methods used in this study include literature review and literature analysis. The research aims to provide a detailed explanation of the phenomenon of online transportation usage in the era of advanced technology.